AN ANALYSIS OF TOTAL PHYSICAL RESPONSE (TPR) IN TEACHING ENGLISH VOCABULARY TO DEAF STUDENTS AT SLB NEGERI 1 MAKASSAR - Wiranto, Muhammad (Language and Education Journal, 2024)
This research examined the teachers’ difficulties in implementing TPR to teach English to students with impaired hearing at SLB Negeri 1 Makassar. A descriptive qualitative approach was applied, with data collected through observations, interviews, and documentation. Research evidence shows that TPR, as a gesture and revoicing strategy involving sign language, works for people who are deaf or hard of hearing and helps teach more vocabulary in terms of visual prompts. However, several challenges emerged, such as restricted words used by students, the necessity to explain repeatedly, and other barriers to learning, leading to extensive instructional challenges. All these challenges take extra time and commitment from the teachers to ensure that the student is given the required learning intervention. Thus, though parental assistance, pictures, and natural objects may be used to support the material, the paper determines that TPR alone lacks effectiveness in overcoming all difficulties.